ANALISIS PERLAKUAN AKUNTANSI PIUTANG PADA USAHA SIMPAN PINJAM PADA KOPERASI - Susanti, Susi; Aminuyati, Aminuyati; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this research is to know Accounting Receivables Accounting Analysis on Savings and Loans at Primary Cooperative of West Kalimantan Regional Police. This research is a type of descriptive evaluative research. The subject of this research is Primary Cooperative of Regional Police of Kalimantan. From the analysis obtained through interviews with the chairman of the cooperative (board) cooperatives show that: 1) Accounting Savings and Loans already in accordance with the provisions of SAK. 2) The absence of an allowance account for allowance for doubtful accounts should be presented for the purpose of deleting the special receivables on the balance sheets and special accounts receivable account on the balance sheet should be presented separately from current assets and presented on other assets items. Depreciation value presented in the balance sheet exceeds the asset's acquisition value and must be adjusted. Unpaid tax liability. Payment of rent on the occupied premises. No reports of changes in equity and notes to the financial statements.Keyword : Accounting Receivables Treatment, Savings and Loans. Â